Consideration of environmental factors in reflections on car purchases: Attitudinal, behavioural and sociodemographic predictors among a large UK sample. (1st September 2019) - Chng, Samuel; White, Mathew P.; Abraham, Charles; Skippon, Stephen
Abstract: Encouraging the purchase of low-emission vehicles could reduce the environmental impact of growing global car ownership. To date, however, there is relatively little research into the degree to which environmental features, such as reduced CO2 emissions, are considered important when reflecting on car purchase decisions using large representative samples. This issue was explored using data from wave four (2013/14) of the UK Household Longitudinal Study, weighted to be representative of the UK population ( N = 12, 895). Principal components analysis identified three types of considerations during car purchase reflections: Utilitarian, Image-conscious and Environmental. Logistic and Ordinary Least Squares regressions identified attitudinal, behavioural and sociodemographic predictors of reporting environmental considerations during car purchase. Consideration of environmental factors during reflections on car purchases was more likely among those with higher climate change concerns and topic engagement, as well as self-reported pro-environmental behaviours more generally. Environmental considerations were also higher amongst women, older adults, non-white ethnic groups, urban residents and among individuals in Scotland (vs. London). Contrary to previous findings, richer and more educated respondents were less likely to consider environmental factors, with income positively related to image factors such as brand. Although our findings offer some support for the pro-environmental attitude–behaviour consistency hypothesis, they also highlight key non-attitudinal, sociodemographic factors underlying car purchase reflections that may help social-marketers and policy makers identify key audiences to more effectively promote low-emission vehicle purchases. Highlights: UK respondents were asked what they considered important when buying a car or van. Three factors emerged: 'utilitarian', 'image' and 'environmental', considerations. Climate concern and engagement were positively related to environmental considerations. Daily environmental behaviours were positively related to environmental considerations. Environmental considerations differed significantly across sociodemographic groups.